2020
DOI: 10.1002/tee.23204
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Average Torque Optimization Method of Parallel Magnetized Surface‐Mounted Permanent‐Magnet Machine with Third‐Order Harmonic Shaping Method

Abstract: On the basis of existing studies presented in literature on optimizing permanent magnet (PM) shaping with third harmonic for the tile‐shaped magnetic poles under radial magnetization, this paper proposes a method for PM shape optimization using third harmonic for bread‐shaped magnetic pole under parallel magnetization. Furthermore, the optimal value of third harmonic that should be injected for achieving maximum torque output of a surface‐mounted permanent‐magnet (SPM) motor under parallel magnetization is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Eccentric pole cutting is widely used in surface-mounted motors, and the analytical calculation formula is derived in [4,6,13]. At present, this method is widely used in sintered magnetic tile and less in bonded magnetic ring.…”
Section: Eccentric Pole Cuttingmentioning
confidence: 99%
See 1 more Smart Citation
“…Eccentric pole cutting is widely used in surface-mounted motors, and the analytical calculation formula is derived in [4,6,13]. At present, this method is widely used in sintered magnetic tile and less in bonded magnetic ring.…”
Section: Eccentric Pole Cuttingmentioning
confidence: 99%
“…In some high−precision applications, we often want to obtain a nearly sinusoidal Air−gap flux density distribution [4,5]. At present, the methods that can realize sinusoidal air−gap flux distribution include eccentric pole cutting [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19], eccentric magnetizing fixture [20,21], and Halbach Array [22][23][24]. Halbach Array is a special magnet array, which can concentrate the magnetic field on one side, while the magnetic field intensity on the other side is almost zero.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that when the eccentric distance is equal to the maximum magnetization thickness of the PM, not only can the amount of PMs be reduced, but the total harmonic distortion (THD) of the air gap flux density and the cogging torque can also be significantly weakened. In addition, other methods, such as sine cutting [19,20], inverse cosine cutting [21], and third harmonic cutting [22,23], can also improve the air gap magnetic flux density waveform toward a sinusoidal distribution, thereby reducing its low harmonic content and decreasing the cogging torque and torque ripple. However, for a multi-pole LHPMSM, the complex shape of PMs will greatly increase the production cost, with a large amount of material waste.…”
Section: Introductionmentioning
confidence: 99%
“…Through the eccentric design of the outer diameter of the inner and outer segments of the segmented magnetic poles and a finite element analysis, the proportion of harmonics was effectively reduced. In [16], the Carter coefficient was used to correct the uneven variation of radial thickness caused by cogging, and the design parameters for the lowest total harmonic distortion were obtained by the equivalent magnetic circuit method, so that the radial air-gap magnetic flux density waveform was close to sinusoidal. For the built-in permanent magnet motor, in [17], by adjusting the rotor shape, an effective air-gap flux density was achieved, and the fundamental component of the back EMF was optimized to reduce the harmonic content, to minimize the pulsating torque.…”
Section: Introductionmentioning
confidence: 99%